Individual and Collective Information Acquisition: An Experimental Study - Pëllumb Reshidi; Alessandro Lizzeri; Leeat Yariv; Jimmy Chan; Wing Suen (Center for Economic Studies and ifo Institute (CESifo), 2021)
Many committees—juries, political task forces, etc.—spend time gathering costly information before reaching a decision. We report results from lab experiments focused on such information-collection processes. We consider decisions governed by individuals and groups and compare how voting rules affect outcomes. We also contrast static information collection, as in classical hypothesis testing, with dynamic collection, as in sequential hypothesis testing. Several insights emerge. Static information collection is excessive, and sequential information collection is non-stationary, producing declining decision accuracies over time. Furthermore, groups using majority rule yield especially hasty and inaccurate decisions. Nonetheless, sequential information collection is welfare enhancing relative to static collection, particularly when unanimous rules are used.
Keywords: C91; C92; D72; D83; D87; 330; information acquisition; collective choice; experiments